THE EFFECT OF LIQUIDITY, SOLVENCY, AND PROFITABILITY RATIOS ON FINANCIAL PERFORMANCE IN TELECOMMUNICATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Wati, Rafika; Qristin Violinda; Dhea Rizky Amelia (JURNAL BISNIS KOLEGA, 2024)
The purpose of this study was to determine the effect of liquidity ratio as measured by current ratio (CR), solvency ratio as measured by debt to equity ratio (DER) and profitability ratio as measured by net profit margin (NPM) on financial performance as measured by return on assets (ROA) in telecommunication companies listed on the IDX for the period 2021-2023. This type of research is quantitative and the population in this study are all telecommunications companies listed on the IDX for the 2021-2023 period, totaling 22 companies with purposive sampling techniques with certain criteria totaling 20 companies for 3 years of observation, totaling 60 samples. This study uses secondary data, namely the financial statements of telecommunications companies for 2021-2023 obtained through the official website www.idx.co.id. The statistical data analysis method used is multiple linear regression which is processed using IBM SPSS Stastistic software. The results showed that current ratio (CR) partially has a significant effect on financial performance, debt to equity ratio (DER) partially has a significant effect on financial performance, and net profit margin (NPM) partially has a significant effect on financial performance in telecommunications companies listed on the IDX for the 2021-2023 period. The adjusted R square value is 38.6%, which means that the variation in financial performance as measured by CR, DER and NPM, while the remaining 61.4% is influenced by other variables outside the research model used in this study